Aboveground phytomass stock of the lower tiers of forest vegetation in black alder fern forest type in the south-east of Polesie - Garbaruk, Dmitriy; Uglyanets, Anatoliy; Shumak, Svetlana (Journal of the Belarusian State University. Ecology, 2025)
Assessment of biological productivity of the lower tiers of forest vegetation, especially in hard-to-reach black alder forests is very relevant. Above-ground phytomass of living ground cover in stands of black alder fern forest type (Gluninosa-Alnetum filicosum) was studied by the method of mowing, total projective soil coverage – using digital photography, other cenotic indicators – by traditional methods. The study site was the exclusion zone of the Chernobyl nuclear power plant, coinciding with the boundaries of the Polessky State Radiation and Ecological Reserve, located in the extreme south-east of the Belarusian Polesie. It was found that 44 plant species grow in the living ground cover. An invasive pest species Bidens frondosa L. and a nitrophilous native species Urtica dioica L. dominate. Subdominant with them or co-dominant in various combinations are 10 other plant species characterized by high abundance and located in the upper sublayer of the grass cover. The stock of absolutely dry aboveground phytomass of living ground cover in the black alder fern forest type is 574 (407–872) kg/ha, the total projective soil cover is 72 (48–90) %. High spatial variability of these indicators determined the average correlation dependence between them. The stock of aboveground phytomass and total projective soil coverage by living ground cover, their spatial heterogeneity and temporal variability are influenced by a complex of external environmental factors: species composition and stand density, density of undergrowth and undeforest, weather and climatic conditions, location of forest stands in the relief, distance to objects of the hydro-reclamation network, wild ungulates, and internal factors of grass communities themselves: species composition, abundance and morphometric characteristics of dominant species.